2005
DOI: 10.3748/wjg.v11.i39.6197
|View full text |Cite
|
Sign up to set email alerts
|

Glutamine-supplemented total parenteral nutrition attenuates plasma interleukin-6 in surgical patients with lower disease severity

Abstract: TPN supplemented with Gln dipeptide had no effect on plasma IL-8 levels after surgery. However, Gln supplementation had a beneficial effect on decreasing systemic IL-6 production after surgery in patients with low admission illness severity, and lower plasma IL-6 may improve nitrogen balance in patients with abdominal surgery when Gln was administered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 24 publications
1
19
0
Order By: Relevance
“…These effects promote patient recovery. Gln ameliorates the function of intestinal mucosal cells, lymphocytes, macrophages, and neutrophils (12–15). This amino acid is indispensible for intestinal mucosal epithelial cell metabolism as it improves intestinal mucosal repair and restoration of barrier function of the intestinal mucosa (26,27).…”
Section: Discussionmentioning
confidence: 99%
“…These effects promote patient recovery. Gln ameliorates the function of intestinal mucosal cells, lymphocytes, macrophages, and neutrophils (12–15). This amino acid is indispensible for intestinal mucosal epithelial cell metabolism as it improves intestinal mucosal repair and restoration of barrier function of the intestinal mucosa (26,27).…”
Section: Discussionmentioning
confidence: 99%
“…One of the major procedures which result in severe depletion of glutamine from the skeletal muscles, bringing about muscle loss immunosuppression thus resulting in increased risk for post-operative infection and sepsis is surgery. Various studies have indicated that glutamine supplementation in post-operative patients bring about improvement in their clinical outcome and also their intestinal permeability [9][10][11][12]. However, a conclusive data on this aspect have not been explored much in India.…”
Section: Introductionmentioning
confidence: 99%
“…Parenteral GLN supplementation had a beneficial effect in reducing the systemic production of IL-6 after abdominal operations. Lower IL-6 levels probably improved nitrogen balance in these patients 20 . In our study, the increase in IL-6 levels in both groups ( Figure 6) during the postoperative period signals increased inflammatory response regardless of pre-operative use of L-Ala-Gln.…”
Section: Resultsmentioning
confidence: 99%